EN MINORITET SØGER IDENTITET: Drusisk religiøs identitet i den libanesiske offentlighed - Skovgaard-Petersen, Jacob (Tidsskriftet Antropologi, 1998)
Jakob Skovgaard-Petersen: A Minority in Search of Identity. Druze Religions Identity in the context of the Lebanese Public In recent years a number of Middle Eastem religious minorities have been engaged in redefinitions of their religious identities. One of the impulses for this activity has been the growth of Islamic movements that give strict and narrow definitions of what constitutes proper Islam. Another impulse has been the growing awareness of civil and religious rights of minorities. The Druze in Lebanon constitute such a minority that seeks to establish its proper identity in the aftermath of the Lebanese civil war 1975-90 and the general upheavals in the Lebanese national consciousness. Tracing the history of publications about the once-so-secretive Druze religion, the article explores the tendency to stress an Islamic identity for the Druze religion. This Islamization of Druze religion became apparent in a number of publications in the 1960s but has received a new impetus after the end of the civil war. Since this period more sophisticated arguments have centered on the Sufi character of the Druze holy writings and defended their Islamic character along the lines of Sufi apologetics. The article argues that this increased sophistication and professionalization of the agrument is partly due to the polemics against an Islamic identity of the Druze coming from Sunni and Maronite thinkers, some of whom were writing under Druze pseudonyms during the war. It is also due to a novel understanding of the Druze as a religious public which must be leamt about and adapt its Islamic identity through a public debate.